1990
DOI: 10.1067/mva.1990.24603
|View full text |Cite
|
Sign up to set email alerts
|

End-stage renal disease—Is infrainguinal limb revascularization justified?

Abstract: Reports of reconstructive surgery for peripheral vascular disease have been relatively uncommon in patients with end-stage renal disease. Between 1980 and 1989, 39 patients with end-stage renal disease underwent revascularization of 56 limbs. Fifty-two primary infrainguinal and four secondary infrainguinal bypass grafts were performed. In addition, nine thrombectomies were performed. At the time of surgery 37 patients were on dialysis; three had functioning kidney transplants. The indications for revasculariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 7 publications
2
25
1
Order By: Relevance
“…Infections usually account for most of the remaining mortality observed postoperatively. Harrington et al [26], in their series of 39 ESRD patients with surgical revascularization, reported up to 43% of death related to sepsis. In our study, patients undergoing bypass procedures were at increased risk of infection related mortality but so were also older patients, patients with a prior history of transplantation, and patients with a low hematocrit.…”
Section: Discussionmentioning
confidence: 98%
“…Infections usually account for most of the remaining mortality observed postoperatively. Harrington et al [26], in their series of 39 ESRD patients with surgical revascularization, reported up to 43% of death related to sepsis. In our study, patients undergoing bypass procedures were at increased risk of infection related mortality but so were also older patients, patients with a prior history of transplantation, and patients with a low hematocrit.…”
Section: Discussionmentioning
confidence: 98%
“…amputation or revascularization) is more prevalent among patients with renal insufficiency than in those with normal renal function (1)(2)(3). High serum creatinine is associated with poor long-term outcomes after lower extremity revascularization (4) and numerous small retrospective surgical series of revascularization in patients with advanced renal insufficiency have now shown that these patients are at increased risk for short-and long-term post-operative mortality and graft failure compared to patients with normal renal function (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Some authors proposed using similar criteria for limb revascularization, whether or not the patient had ESRD. 4 This was applied in our study, and the difference in the frequency of revascularization (31% vs 79%, p = 0.0036) was due to the absence of outflow vessels suitable for revascularization in the ESRD group, and the high prevalence of infrapopliteal arterial involvement as judged by arteriography. In this series, endovascular techniques were not performed owing to extensive calcifications and long occlusions, 2 poor predictive factors for the technical success of transluminal angioplasty or subintimal revascularization.…”
Section: Discussionmentioning
confidence: 99%